Structural changes and the role of monetary aggregates in the UK - Bissoondeeal, Rakesh K.; Karoglou, Michail; Binner, Jane M. (Journal of Financial Stability, 2019)
We investigate whether or not monetary aggregates are important in determining output. In addition to the official Simple Sum measure of money, we employ the sophisticated weighted Divisia aggregate. We also investigate whether or not the influence of money on output is time varying using data-driven procedures to identify breaks in the data and conduct estimations for the different segments defined by these breaks. We find that structural breaks do exist in some of the variables under investigation and these do influence the relationship between monetary aggregates and output. However, the official Simple Sum aggregate appears to be more affected by the breaks than the theoretically superior Divisia aggregate. In particular, our results show that in some segments of our data, the Simple Sum aggregate does not influence output significantly whereas the Divisia aggregate maintains a significant relationship with output in all segments. We conclude that Divisia money is still influencing output in spite of the diminished role played in monetary policy. Our investigation also suggests that the recovery from the financial crisis using quantitative easing would have been faster if money was not being hoarded.